(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. La decisione (in sintesi): una soluzione subottimale - 3. Il ruolo determinante del principio supremo di laicità - 4. Laicità sostanziale, laicità procedurale, accomodamento ragionevole - 5. Discriminazione diretta e indiretta. - 6. Conclusioni. The crucifix ‘accommodated’. Considerations at first reading of the judgment no. 24414/2021 by the United Sections of the Italian Supreme Court of cassation ABSTRACT: With decision no. 24414/2021 the United Sections of the Italian Supreme Court of cassation have provided an unprecedented solution to the issue of religious symbols in the classrooms of public schools. In this essay the author analyses the judgment, focusing in particular on three aspects: the relationship between the so-called ‘Italian principle of secularism’ and the reasonable accommodation; the existence or not of discrimination against the teacher who has been obliged to teach under the crucifix; the practical ways in which this ruling can become ’living law’ in the Italian legal system.